ON THE SCIENTIFIC-BIOBIBLIOGRAPHIC RESEARCH OF "UZBEK FOLKLORE" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The examples of folklore that have been refined over the centuries from our thoughtful ancestors are a true spiritual heritage. In recording, publishing and researching these priceless masterpieces, hardworking scientists and selfless folklore collectors have done a great job. The monograph "Uzbek Folklore Studies" by the famous folklorist scientist M. Jorayev is a large-scale scientific and biobibliographic study written about the effective scientific and creative activities of Uzbek folklorists. The article talks about this book.